Susceptibility profile to antifungals of Candida spp. isolated from infants and children (Revista Contexto & Saúde, 2025)
Pediatric candidiasis and candidemia are important causes of morbidity and mortality worldwide. This study aimed to analyze the incidence and antifungal susceptibility profile of Candida. spp. isolated from infants and children in maternity wards and public hospitals. This is a retrospective, analytical-cross-sectional observational study carried out through the analysis of data from medical records and the antifungigram of patients diagnosed with candidiasis or candidemia admitted from January 2015 to December 2021 in the city of São Luís-MA. A total of 627 episodes of Candida infection were observed (45.3% female and 54.7% male). The highest incidence occurred within the age groups of 1-3 months (41.63%) and 1-3 years (22.65%) and the main isolated species were C. albicans, C. parapsilosis and C.tropicalis. The highest diversity of pathogenic Candida was detected in blood, mid-stream urine, and tracheal secretions (p
Keywords: Candidiasis; Candidemia; Antifungal resistance